ANALISIS KEPUASAN NASABAH MELALUI KEPRCAYAAN NASABAH, KUALITAS LAYANAN DAN KUALITAS PRODUK (STUDI KASUS PADA KOSPIN JASA CABANG WELERI) - Firdaus Firdaus (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2019)
The very tight dynamics of business competition requires business actors to prioritize customer satisfaction so that consumers or customers do not move to other companies. One strategy that can be used by business people by increasing customer satisfaction. High customer satisfaction will facilitate business success, in this case customer satisfaction is seen as the spearhead in retaining customers. This study aims to examine the factors that influence customer satisfaction at Kospin Jasa Weleri Branch. This data research uses a questionnaire with a sample of 100 respondents in the Weleri region with a total number of questionnaires as much as 94. This sampling technique uses probability sampling, with one of the methods used is purposive sampling. The data obtained were then analyzed with the SPSS program. The results of this study are: (1) Customer trust has a positive and significant effect on Customer Satisfaction. (2) Service Quality has a positive and significant effect on Customer Satisfaction. (3) Product Quality has a positive and significant effect on Customer Satisfaction. (4) simultaneously customer trust, service quality, and product quality have a positive and significant effect on customer satisfaction in customer service branch Weleri.